EXPERIMENTAL STUDY ON PROPERTIES OF CONCRETE USING FINELY GROUND FLY ASH - Maruoka, Masanori; Kanazawa, Koudai; Fujiwara, Hiromi (Cement Science and Concrete Technology, 2025)
Silica fume, which is an admixture for high-strength concrete is currently not manufactured in Japan and can only be obtained by importing it from abroad. Therefore, it is very expensive in Japan. On the other hand, fly ash is produced in large quantities in Japan, and desired to be used for effective utilization. Therefore, in this study, it was focused on ground fly ash for alternative admixtures for high strength concrete, and examined the possibility of obtaining properties similar to silica fume. In this study, by using finely pulverized fly ash in concrete, it was expected to develop strength comparable to that of silica fume. In the experiment, it was examined the fresh and hardened properties of concrete and mortar using finely ground fly ash and silica fume. In fresh properties, it was found that dilatancy properties appeared in concrete using finely ground fly ash. Therefore, the method to suppress it was examined.As a result, by substituting 20％ cement for fly ash pulverized to an average particle size of about 1.5μm, it was confirmed that the concrete show the same level of strength development as concrete with 10％ silica fume replacement, and also exhibit good fresh properties.